Review of the Eprinomectin effective doses required for dairy goats: Where do we go from here? - Rostang, Antoine; Devos, Jacques; Chartier, Christophe (Veterinary parasitology, 2020)
•Eprinomectin is one of the few anthelmintics with a zero-day milk withdrawal period.•Exposure to Eprinomectin is strongly reduced in lactating goats compared to dry.•The dose appears to be suboptimal to prevent the development of parasite resistance.•The Pour-on route suffers from a very strong inter-individual variability.•There is an urgent need to review and discuss the use of Eprinomectin in goats. Eprinomectin (EPM) has been recently granted a marketing authorisation in the European Union for use in goats, with a zero-day milk withdrawal period. Considering the high prevalence of benzimidazole resistance worldwide and the economic implications of managing milk residues, EPM may today be considered the main (or even the only) affordable treatment option, at least in dairy goats in the EU. However, the chosen dose (1 mg/kg) seems to be suboptimal, especially for lactating goats, and the chosen route of administration (Pour-on) highly subject to inter-individual variability. Considering the scarcity of anthelmintic resources, such a dosage regimen might threat the sustainability of this crucial drug in goat milk production and needs to be urgently discussed and reassessed.